Visualizações de informações em dispositivos multitoques - Lammel, Felipe Eduardo (2014)
Nowadays, the Internet presents itself as a valuable source of data because it has a multitude of users with very different profiles, feeding it every day. This large amount of data generates useful information for businesses and other users who use them with some specific purpose. However, not all these data are actually useful and certainly need to be filtered to a better understanding. In this context, Information Visualization techniques have aided the analysis of these data types facilitating their understanding and reducing the chances of misinterpretation. With the popularity of multi-touch devices, it is essential to devise alternatives for applications using these techniques so that they can be used with this technology as well. Moreover, these technologies may perhaps add value to these techniques since they provide a more immersive way of interacting. In this context, this work aims to determine how the analysis of data through information visualization techniques can be improved from interactions with multitouch devices. To accomplish this research has been done in the areas of information visualization, social networking, and multi-touch technology. It has also developed a prototype tool that utilizes information visualization techniques and this was put to use for later analysis of the data obtained. In addition to the implementation of the tool was applied a process for the preparation of multitouch gestures to define which of them should be implemented using the point of view of users.